2022
DOI: 10.1080/21655979.2021.2017695
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous H 2 S reverses high glucose-induced endothelial progenitor cells dysfunction via regulating autophagy

Abstract: This study aims to determine the effect of exogenous hydrogen sulfide (H 2 S) under high glucose (HG)-induced injury in endothelial progenitor cells (EPCs), and to explore the possible underlying mechanisms. Mononuclear cells were isolated from the peripheral blood of healthy volunteers by density-gradient centrifugation and identified as late EPCs by immunofluorescence and flow cytometry. EPCs were treated with high concentrations of glucose, H 2 S, Baf-A1, 3-MA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Melatonin can promote autophagy and inhibit ECs apoptosis in an autophagy-dependent manner 93 . Ma et al reported that exogenous hydrogen sulfide ameliorated high glucose-induced EPCs dysfunction by promoting autophagy 94 . In addition, activation of autophagy also plays an important role in the induction of angiogenesis.…”
Section: Roles Of Autophagy In Diabetic Wound Healingmentioning
confidence: 99%
“…Melatonin can promote autophagy and inhibit ECs apoptosis in an autophagy-dependent manner 93 . Ma et al reported that exogenous hydrogen sulfide ameliorated high glucose-induced EPCs dysfunction by promoting autophagy 94 . In addition, activation of autophagy also plays an important role in the induction of angiogenesis.…”
Section: Roles Of Autophagy In Diabetic Wound Healingmentioning
confidence: 99%
“…The protective effect of sulfide in several illnesses has been linked to its role promoting autophagy which may decrease ROS production. In a recent study in endothelial progenitor cells (EPCs), exogenous H 2 S ameliorated the high glucose (HG)-induced injury by promoting autophagic flux and decreasing ROS production, demonstrating the protecting role of sulfide under this dysfunction [ 62 ]. Their findings demonstrated that the phosphorylation of the endothelial nitric oxide synthase (eNOS) at Thr495 determines whether this enzyme produces either NO or superoxide, and sulfide reduced the phosphorylation level of this enzyme, decreasing NO and ROS production [ 62 ].…”
Section: Hydrogen Sulfide As a Regulator Of Autophagymentioning
confidence: 99%